The Effect Of Highly Challenging Balance Training On Balance In Parkinson's Sufferers: Critical Review - Wahyuni Wahyuni; Nur Agung Martopo (Prosiding University Research Colloquium, 2022)
Parkinson's is a progressive neurodegenerative disease, characterized by several motor symptoms such as tremor, bradykinesia, rigidity or stiffness, and postural instability. Balance problems, or postural instability, are one of the main motor symptoms of Parkinson's disease that usually appear in the later stages of the disease. The purpose of this study is the effect of highly challenging balance training on balance in Parkinson's patients based on the existing literature and to find out the highly challenging balance training exercise in Parkinson's patients based on the existing literature. The method of this research is to use a critical review study. From the results of this study, it was found that 7 out of 156 articles matched the inclusion criteria. In this study, 7 articles were used as the basis for further studies for the appraisal stage. The results of the appraisal show that 6 articles have a Quartile 1 (Q1) value and 1 article has a Quartile 3 (Q3) value. Based on the results of studies that have been conducted on the effect of highly challenging balance training on balance in Parkinson's patients as concentration using the Critical Review system, it can be concluded that highly challenging bal